Folklore and Folklife in the United Arab Emirates - Hurreiz, Sayyid Hamid (Routledge, 2002)
Traditional lifestyle of Emirati people, including customs and rituals, traditional medicine, cultural festivals, material culture and literature. A unique description and analysis of the domains and genres of UAE folklore, including folk customs and beliefs, traditional arts and crafts, folk dances, folk narratives and proverbs. Challenging the established meaning of folklife, this volume also deals with folklore in public life, in the mass media, in education and in politics.
Introduction -- Chapter 1 The United Arab Emirates -- Chapter 2 The State of Folklore Studies and Research in the UAE -- Chapter 3 Folklore in Private and Public Life -- Chapter 4 Folklore and the State -- Chapter 5 Folk Literature -- Chapter 6 Folk Customs and Beliefs -- Chapter 7 Folk Medicine -- Chapter 8 Performing Folk Arts -- Chapter 9 Material Culture -- Conclusion
English
Keywords: GR99.6-390 Geography, anthropology, recreation - Folklore- By region or country; UAE